Fraudulent financial reporting and earnings management in Shariah compliant companies - Muda, Razali; Jamaludin, Azahari; Hamdan, Hamdino; Muhd Kulal, Salamiah (2025)
Fraudulent financial reporting and earnings management have been significant concerns for investors, regulators, and scholars since the 1940s, impacting the allocation of resources in the economy and the credibility of financial reports. While most research has focused on developed markets like the U.S. and Europe, there is a notable lack of studies in Asian and emerging markets, especially within Shariah compliant companies, highlighting the importance of this study. The increase in fraudulent financial reporting and earnings management threatens market integrity and decision-making, leading to substantial losses subsequent to its exposure. Moreover, such practices contravene the foundational principles of Shariah compliance. This study aims to explore the impact of pressure, opportunity, and rationalisation on the probability of fraudulent financial reporting and earnings management preceding the year of fraudulent activity in public listed Shariah compliant companies. It employs the Fraud Triangle Theory and utilizes two quantitative models: the Beneish M-Score model to evaluate the likelihood of fraud and the Modified Jones model to identify earnings management. The samples were sourced from Bursa Malaysia and Securities Commission databases, targeting firms convicted of fraud and earnings management between 2014 and 2023. Eight proxies were analysed: leverage (LEV), liquidity (LIQ) and performance (ROE) for pressure; audit firm size (AUDS) and CEO duality (CEOD) for opportunity; and board independence (BODIND), related party transactions (RPT) and founder on the board (FOUND) for rationalisation. The study anticipates positive relationships between pressure, opportunity and rationalisation to fraud and earnings management, with fraud directly linked to previous instances of earnings management. This study contributes to the literature on fraud and earnings management in Shariah compliant companies, supports regulatory authorities in enhancing detection and prevention mechanisms, and facilitates informed decision-making for investors based on reliable financial reporting, besides confirming the applicability of the Beneish M-Score model and Modified Jones models to emerging markets like Malaysia.